KARAKTERISTIK SARANG DAN TUMBUHAN SUMBER GETAH PROPOLIS LEBAH TAK BERSENGAT (Stingless Bee) DARI BUTON UTARA - Pujirahayu, Niken; Hardianto, Fani; Mando, La Ode Agus Salim; Uslinawaty, Zakiah; Rosmarlinasiah, Rosmarlinasiah; Basruddin, Basruddin (Universitas Pattimura, 2022)
This study aims to determine the bee species, nest characteristics and identify the stingless bee propolis plant source from Kulisusu District, North Buton Regency. This research uses the purposive sampling method in searching nests, and the data is processed descriptively. Samples of stingless bees were taken from four hives from three sampling locations. The characteristics of the nest observed were the shape of the nest entrance, color and size (length and diameter), and the type of entrance opening. The stingless bees found belonged to the genus Tetragonula and consist of two species, Tetragonula sapiens, and Tetragonula fuscobalteata. The shape of the nest entrance varies (without funnel, short funnel, and cylindrical funnel) with black, brown, or blackish-brown color. The diameter of the nest entrance was between 3 to 5 cm with the type of opening (triangular, irregular, and oval). Nine plants were identified as sources of propolis in each nest, and two of them, Anacardium occidentale (cashews) and Schleichera oleosa (Kesambi), were found in all observed nests.